Auditory event-related potentials associated with perceptual reversals of bistable pitch motion - Davidson, Gray D.; Pitts, Michael A. (Frontiers in Human Neuroscience, 2014)
Previous event-related potential (ERP) experiments have consistently identified two components associated with perceptual transitions of bistable visual stimuli, the "reversal negativity" (RN) and the "late positive complex" (LPC). The RN ( 200ms post-stimulus, bilateral occipital-parietal distribution) is thought to reflect transitions between neural representations that form the moment-to-moment contents of conscious perception, while the LPC ( 400ms, central-parietal) is considered an index of post-perceptual processing related to accessing and reporting one’s percept. To explore the generality of these components across sensory modalities, the present experiment utilized a novel bistable auditory stimulus. Pairs of complex tones with ambiguous pitch relationships were presented sequentially while subjects reported whether they perceived the tone pairs as ascending or descending in pitch. ERPs elicited by the tones were compared according to whether perceived pitch motion changed direction or remained the same across successive trials. An auditory RN component (aRN) was evident at 170ms post-stimulus over bilateral fronto-central scalp locations. An auditory LPC component (aLPC) was evident at subsequent latencies ( 350ms, fronto-central distribution). These two components may be auditory analogs of the visual RN and LPC, suggesting functionally equivalent but anatomically distinct processes in auditory versus visual bistable perception.